2016
DOI: 10.1007/s00709-016-1003-x
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of plant and rhizospheric microbiota as stable interactomes

Abstract: The growing human population and depletion of resources have necessitated development of sustainable agriculture. Beneficial plant-microbe associations have been known for quite some time now. To maintain sustainability, one could show better reliance upon beneficial attributes of the rhizosphere microbiome. To harness the best agronomic traits, understanding the entire process of recruitment, establishment, and maintenance of microbiota as stable interactome within the rhizosphere is important. In this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 81 publications
0
23
0
Order By: Relevance
“…However, this competition also depends on the ecological environment. Under stressful conditions, such as low nutrient availability, plant responses to the competition between AM and other microorganisms may change, for example, from synergistic to antagonistic, and affect plant performance [57]. Miransari et al [49] revealed that, when the soil is highly compacted, competition for soil resources among soil microorganisms, including AM fungi and other microbes, increases.…”
Section: Discussionmentioning
confidence: 99%
“…However, this competition also depends on the ecological environment. Under stressful conditions, such as low nutrient availability, plant responses to the competition between AM and other microorganisms may change, for example, from synergistic to antagonistic, and affect plant performance [57]. Miransari et al [49] revealed that, when the soil is highly compacted, competition for soil resources among soil microorganisms, including AM fungi and other microbes, increases.…”
Section: Discussionmentioning
confidence: 99%
“…The ‘DADA2’ package (v 1.10.1) (78) within the Bioconductor software environment (v 3.8) (79) of the R Project (v 3.5.2) (80) was used to process raw sequencing reads. All reads were initially quality filtered using the ‘filterAndTrim’ command with default settings (“maxN=0, maxEE=c(2,2), truncQ=2”). To avoid computational limitations resulting from the fact that multiple libraries contained >>100000 reads, the resulting high-quality reads of libraries were randomly down-sampled to 15000 paired-end reads (BioProject ID: PRJNA591021).…”
Section: Methodsmentioning
confidence: 99%
“…The rhizobiome has long been recognized to have important impacts on plant growth and health (1). The microbes of the rhizobiome, which directly interact with and are influenced by the roots (2), can benefit their plant hosts through recycling and producing bioavailable nutrients (35), increasing disease resistance through competition with or inhibition of pathogens (6), and influencing plant growth and stress tolerance through production of phytohormones (7, 8). Community composition within the rhizobiome is shaped by plant metabolism and physiology, which controls rhizodeposition, exudation of organic carbon and nitrogen, and release of defense compounds (7, 9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…Rhizospheric microbiota (RM) is a vital component of the rhizosphere ecosystem in lakeshore areas. The interaction of plant roots with innumerable microbial communities within this niche has a considerable impact on developmental stages of lakeshore plants and their tolerance to stressful conditions (Shilev et al, 2001;Dennis, Miller & Hirsch, 2010;Gill et al, 2016;Bandyopadhyay et al, 2017). For instance, higher plant growth and biomass were obtained when bacteria selected from metal-contaminated soil were added to experimental soil (Shilev et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Plant-associated microbes are considered as “helpers” that can provide additional genes to the host for acclimatization of the latter in changing or distinctive environmental conditions ( Vandenkoornhuyse et al, 2015 ), although they also associated with soil-borne microbial diseases ( Mao et al, 2019 ; Mao et al, 2020 ). Recently, the recruitment of RM into the rhizosphere gained much attention among researchers ( Standing et al, 2005 ; Bandyopadhyay et al, 2017 ; Zhang et al, 2019 ; Kavamura et al, 2020 ). Related studies with terrestrial plants have shown that the factors influencing microbial recruitment include plant genotype and age, edaphic factors, geographical location, and climatic changes ( Berg & Smalla, 2009 ; Bulgarelli et al, 2012 ; Tkacz et al, 2015 ; Bandyopadhyay et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%